Analisis Segmentation, Targetting, And Positioning Garam Umami Rendah Natrium - Adiningrum, Aqilah Rahma; Panjaitan, Adrian; Kusuma, Ailsa Seca; Shafina, Keisha; Setiawati, Indah (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
The trend of healthy products has a big chance on the market. One of them is Losspaper, which is a low-sodium salt product made from boiled salt, seaweed extract, and genjer as a solution to prevent hypertension. As a new product on the market, research is needed to determineSegmenting, Targeting, and Positioning, as well as marketing strategies to find out the market potential of Losspaper products.The source of research data is primary data obtained by using a questionnaire technique using the Google Form platform as media. The analytical methods used were validity, reliability, cluster analysis, and cross-tabulation using the SPSS 26.0 program to be interpreted descriptively.Determination of STP and marketing strategy is based on the demographic and psychographic characteristics of consumers.The results showed that low-sodium salt has a fairly high market opportunity for consumerswith the last education level of high school/equivalent, no history of hypertension, enough to know how to prevent hypertension, and for consumers who have never consumed low-sodium salt. The right marketing strategy for Losspaper is in the form of maintaining quality, price adjustments, and market development through partners and product promotion.